2015
DOI: 10.1590/0100-69912015005004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the oropharyngo-laryngoscopic findings and the severity of obstructive sleep apnea

Abstract: Original Article Original Article Original Article Original Article Original Article DOI: 10.1590/0100-69912015005004 Correlation between the oropharyngo-laryngoscopic findings and Correlation between the oropharyngo-laryngoscopic findings and Correlation between the oropharyngo-laryngoscopic findings and Correlation between the oropharyngo-laryngoscopic findings and Correlation between the oropharyngo-laryngoscopic findings and the severity of obstructive sleep apnea the severity of obstructive sleep apnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Changes in uvula structure corresponded to more severe results in polysomnographic examination. In addition, the presence of edema was significantly related to mild and / or moderate outcome (25) . It is known that upper airways soft tissue size -such as the uvula -is determined by genetic conditions but can be affected by environmental factors such as inflammation, infection and infiltration by metabolic components, alternating the tone and shape of the muscles of these structures, predisposing to narrowing and collapse during sleep (26) .…”
Section: Discussionmentioning
confidence: 94%
“…Changes in uvula structure corresponded to more severe results in polysomnographic examination. In addition, the presence of edema was significantly related to mild and / or moderate outcome (25) . It is known that upper airways soft tissue size -such as the uvula -is determined by genetic conditions but can be affected by environmental factors such as inflammation, infection and infiltration by metabolic components, alternating the tone and shape of the muscles of these structures, predisposing to narrowing and collapse during sleep (26) .…”
Section: Discussionmentioning
confidence: 94%
“…However, it is known that these patients have lower sleep quality (17,18). In addition, since the need for sleep and daytime sleep is higher in this population, the transition to sleep is faster (19). Therefore, it was thought that they might need sleep medication less than the normal population.…”
Section: Discussionmentioning
confidence: 95%
“…This reinforces the importance of analyzing the factors together and in a context. Findings from Dias et al ( 2015) 16 and Araújo-Melo et al (2016) 17 showed that Mallampati classification is a predictive factor that presents considerable changes even in people without the disease.…”
Section: Discussionmentioning
confidence: 98%